Coping strategies of family caregivers in spinal cord injury: a qualitative study. Issue 2 (16th January 2022) - Zanini, Claudia; Fiordelli, Maddalena; Amann, Julia; Brach, Mirjam; Gemperli, Armin; Rubinelli, Sara
Abstract: Purpose: To identify the coping strategies used by family caregivers of persons with spinal cord injury (SCI) in Switzerland in order to develop tailored support programs. Materials and methods: Purposive sample of >18 years participants, speaking an official Swiss language fluently, being family caregivers of persons with SCI for at least 4 years, and perceiving either a high or low burden in relation to caregiving. Data were collected through face-to-face semi-structured interviews ( N = 22). Thematic analysis was performed. Results: Four main coping strategies were identified: reappraisal, active acceptance, setting limits to the caregiver role, and seeking support. These strategies can be used one at a time or combined, and at different times of a caregiver pathway. Our analysis highlighted that caregivers need skills to implement these strategies (e.g., self-evaluation skills). Conclusions: Caregivers of persons with SCI develop cognitive coping strategies to make sense of the situation and establish a "new normal" and problem-focused coping strategies to deal with their new tasks and role. These strategies do not seem to be typical only of SCI caregivers. Hence, interventions that worked for caregivers in other fields could be adapted. Rehabilitation centers should systematically integrate programs targeted to caregivers into their offerings. IMPLICATIONS FOR REHABILITATION: Healthcare systems need to develop educational and support measures for both persons with a health condition and their caregivers. Caregivers should become long-term partners in rehabilitation and a regular and structured needs assessment should be offered. Interventions that worked for caregivers in other fields can be adapted to support also caregivers in SCI. Educational and support programs dedicated to caregivers should teach not only how to perform caregiving tasks but also how to balance between responding to the care recipient's needs and their own needs.